An Australian Fuel Substitution - Hall, V.B; Truong, T.P; Van Anh, Nguyen (School of Management Working Papers, 1990)
Over the past ten years, the revenue collected by Australia's Commonwealth government from excises and royalties on liquid fuels has increased substantially. These revenues have risen from around six per cent of total taxation in 1975-76 to nearly 12.5 per cent in 1985-86, and from 43.6 per cent of total excise revenue to 76 per cent over the same period (Figure 1). The proportion of liquid fuels excise and royalties raised from each of crude oil and petroleum products has also varied considerably, and changed particularly dramatically during 1986-87 (Figure 2). These changes have been induced variously by movements in volumes produced and demanded and by policy decisions affecting import parity prices and tax rates. For example, it is clear from Figure 3 that the dramatic fall in crude oil revenue can be associated with falls in all three of the import parity price, the crude oil levy rate, and the production of indigenous crude. But in Figure 4, the corresponding substantial increase in products revenue is most closely aligned with an increased excise rate. A major general purpose of this paper is therefore to identify the principal aggregate and structural impacts which result from a substantial switch to petroleum products excise revenue from crude oil levy revenue. Industrial ·sector interfuel substitution effects are explicitly allowed for, under conditions of no net change in nominal or real liquid fuel tax receipts. Specific account is also taken of two important strands of the Australian government's pre-1988 oil regulatory framework, namely the import parity pricing (IPP) and domestic allocation systems for crude oil.